The Relationship Between Job Stressor and the Intention to Leave : A Case of PTPL Ampang College - Mazlina, Che Malek (2012)
This article examine the relationship between of job stress and the intention to leave. The determinants of job stress that have been examined under this study include role conflict, role ambiguity and role overload. This study was done among 51 employees from PTPL Ampang College regardless their position, lenght of service and work nature in company .Data were gathered through questionnaires and was being analyzed using Statistical Package for Social Science (SPSS) version 17. Throughout the statistical analysis using correlation analysis, it is found that there is a significant relationship between Job stress and intention to leave. Among all the dimensions of Job stress, role conflict is found to be the most independent variable in driving the intention to leave among staff at PTPL Ampang College.